Emerging Functions of Nano-Organized Polysaccharides - Kitaoka, Takuya (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Natural polysaccharides, such as cellulose and chitin, possess unique hierarchical nanoarchitectures that can never be artificially reconstructed, and their nano-organized structures are involved in the hidden materials functions with great potential. Pioneering the emerging functions of nano-organized polysaccharides will break through to achieve the Sustainable Development Goals.